A revival dictated by necessity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The negotiation of free trade agreements with the major trading blocs, and especially with the European Union, is fueling a revival of interest in ACP regional economic communities. But it remains to be seen if the creation of these accords will translate